The Impact of Information and Communication Technology (ICT) on Teaching and Learning of Igbo Drama in Nigeria Tertiary Education (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This paper evaluates the impact of information and communication technology(ICT)on the lgbo drama teaching and learning in Nigeria tertiary education. Teaching and learning of lgbo drama in Nigeria mostly depends on traditional approaches. However, it cannot be ruled out that the use of traditional method of teaching was face to face mode. This mode of teaching and learning has been variously viewed as not being able to meet the digital age. ICT has transformed the traditional approaches on the Igbo drama teaching and learning, by providing the students access to ICT application such as Digital library, E-learning, website etc. One of the importance of ICT on the lgbo drama teaching and learning is that with ICT, Students can discuss and share information with others, including experts in the field, either directly (one to one) or through online social communities such as Facebook, Myspace, Google and Twitter. This enables the students to stay motivated and acquire skills which they will need in their future lives. This is a survey research. The theory adopted was Piaget Theory of Learning. The study revealed some challenges of using ICT on the lgbo drama teaching and learning such as inadequate power supply, lack of knowledge of ICT from both the teachers and the students. The study recommended that adequate power supply should be made available to Nigeria higher institutions, ICT should be compulsorily included in lgbo drama curriculum, admission requirement and teachers’ employment should be based in the knowledge of ICT by the applications.
Keywords: ICT; Drama; Education; Communities; Teaching Learning